Innovative Work Behavior Karyawan Swasta Bagian Marketing Di Solo Raya: Ditinjau dari Organizational Justice dan Entrepreneurial Leadership - Ariyani Wahyu Wijayanti (Universitas Veteran Bangun Nusantara, 2023)
This study aims to examine the effect of organizational justice and entrepreneurial leadership on innovative work behavior of private marketing employees in Solo Raya. The sample in this study were private marketing employees in Solo Raya as many as 97 respondents. The analytical tool used to determine the effect between the independent and dependent variables using multiple linear regression. Based on the results of the analysis, it shows that organizational justice and entrepreneurial leadership variables have a positive effect on innovative work behavior. With the implementation of good and balanced organizational justice and entrepreneurial leadership in a company, it will be able to create a comfortable work environment so that employees feel confident to introduce new ideas that they encounter.